Mechanisms for Activating the Personal Potential of Students in the Context of Digitalization of University Education - E. N. Shutenko; A. I. Shutenko (Высшее образование в России)
The purpose of this paper is to design a psychological-pedagogical construct of the implementation of information technologies in the process of teaching students for developing their personal potential. The rapid digitalization of higher education has caused the need to ensure the didactically correct information-communicative technology (ICT) introduction in education, which must organically comply with the structure and logic of the learning process, as well as the task of personal development. Solving these tasks, the authors propose not direct, but mediated use of different ICTs through the development of a system of various educational communications that are built and supported by the teacher. This is the novelty of the study and its dissimilarity to most of the current projects of forced, technocratic digitalization of students study, which do not sufficiently take into account the laws and principles of a holistic educational process and the becoming of personality in it.Based on psychological and didactic approaches and methods, the authors reconstruct the pedagogically controlled process of ICT introducing into education through the implementation by the teacher of interrelated mechanisms – environment-forming and trigger mechanisms. The environment-forming mechanism unfolds the logic of the phased introduction of ICT – from the principles of their use through the construction of educational communications to the methods for activating of students personal potential in the form of trigger mechanisms. These activators are modes for the practical inclusion of ICT in education and are set by the mechanism for personalizing educational communications. Assuming the attunement of ICT to the personality of the student, this mechanism brings the teacher to the fore in the process of digitalization of learning. Being the initiator and organizer of educational communications, the teacher can adequately and fully ensure this attunement and targeting of ICT use by implementing a set of conjugated mechanisms: responsive, polycontact, contemporal, meaning-centric, project-constructing, cultural-mediating, consolidating, inclusive, comparative and the mechanism of problematization.Approbation of the proposed mechanisms in the practice of online-learning has shown their sufficient effectiveness, students have an increase in indicators of self-realization and self-regulation, as well as the significance of values of self-development in education.